Governance: A Source to Increase Tax Revenue in Pakistan - Muhammad Shahid Hassan; Haider Mahmood; Muhammad Naveed Tahir; Tarek Tawfik Yousef Alkhateeb; Ayesha Wajid (Complexity)
Improved governance in any economy indicates government stability, secured law and order, and minimum internal and external conflicts. A higher level of governance may demonstrate the healthy performance of economic activities and tax revenue collection. Hence, it is vital to investigate the relationship between governance and tax revenue collection in any developing country. Therefore, we aim to investigate the impact of governance on tax revenue in Pakistan using control variables inflation and industrial value-added. The Autoregressive Distributive Lag (ARDL) cointegration technique is utilized to find the long- and short-run effects of hypothesized variables on the tax revenue using a period 1976–2019. After employing a cointegration on the hypothesized model, the results expose that government stability, law and order, and internal and external conflicts leave a positive and significant impact on tax revenue in the long and short run. Hence, it is concluded that governance is an essential source in expanding tax revenue in Pakistan. Moreover, industrial value-added and inflation also show positive effects on the tax revenue. On the grounds of these results, it is proposed that the government should make serious efforts to improve governance and industrial activities for better tax revenue collection.